Placental biomarkers for the prediction of neurodevelopmental disorders - Patel, Payal; Ku, Joy; Uzoaru, Ike; Goldstein, Jeffery A. (Frontiers in Cell and Developmental Biology, 2025)
Neurodevelopment shapes how children think, move, and engage with their surroundings. Understanding the pathways underlying neurodevelopmental pathophysiology in the perinatal stage can inform intervention strategies to mitigate or reduce the severity and extent of developmental brain injuries. Early risk stratification enables timely therapies and resource planning during a critical period for the developing brain. Over the past decade, attention has turned to the placenta as a uniquely informative vantage point for the identification of pregnancies at high risk for adverse neurodevelopmental outcomes. Situated at the maternal-fetal interface, the placenta functions as a dynamic record of intrauterine conditions, integrating genetic and environmental signals into distinct and quantifiable biomarkers. Emerging evidence indicates these placental biomarkers may predict later neurodevelopmental outcomes, highlighting the organ’s value in precision perinatal care. With this in mind, the objective of this scoping review will be to investigate the current use of placental biomarkers as predictors of neurodevelopmental outcomes in clinical practice, particularly the trisomies (T13, T18, T21). In the second section of this paper, we will focus on recent advancements and improvements in the use of placental biomarkers for diagnostic and prognostic purposes in other neurodevelopmental outcomes. Finally, this article concludes with a discussion of the impact of neuroplacentology in protocol development, risk stratification, and psychosocial wellness of pregnant women.